Modeling Tourist Interest in Visiting Halal Tourist Destinations in West Nusa Tenggara (NTB): A Systematic Literature Review - Primadona, Fitry; Hartoyo, Hartoyo; Yuliati, Lilik Noor; Arsyianti, Laily Dwi (Economica: Jurnal Ekonomi Islam, 2024)
Halal tourism is a growing market segment driven by the increasing demand for travel experiences that adhere to Islamic principles. As the global Muslim population continues to expand, the prospects for halal tourism are substantial, with significant market value and robust growth trends. Indonesia, with its diverse attractions like West Nusa Tenggara (NTB), plays a strategic role in this sector. This study investigates the factors influencing tourist intentions to visit NTB's halal destinations, employing a systematic literature review using the PRISMA technique. Key factors impacting tourist intentions include the availability of halal food, halal accommodation, halal tourism promotion, and the socio-cultural environment. Additionally, halal certification and effective promotional strategies serve as partial moderators, enhancing these influences on tourist decision-making. The findings provide valuable insights for policymakers and stakeholders, offering a model for attracting and retaining tourists in halal destinations. This research contributes uniquely by providing a comprehensive analysis of tourist intention factors within NTB's halal tourism context, supporting sustainable and inclusive tourism development.